Production of composite clay bricks: A value-added solution to hazardous sludge through effective heavy metal fixation. (20th March 2019) - Kulkarni, Vihangraj V.; Golder, Animes Kumar; Ghosh, Pranab Kumar
Highlights: Commercially viable and green technique utilizing hazardous sludge in bricking. Bricks substituted with 20% sludge complied both ASTM and Indian Standards. Ductile behavior of sludge added bricks could avoid catastrophic masonry failures. Production of yellow colored decorative imparted by CaO in sludge. Highly effective heavy metals fixation and insignificant metal leaching in TCLP. Abstract: The study explores utilization of hazardous battery sludge in fired clay brick production with the conjoint aim of reducing depletion of fertile clay and heavy metal fixation. Spectroscopic analysis of pulverized clay soil (PCS) and pulverized battery sludge (PBS) revealed presence of fluxing agents viz. K2 O, Fe2 O3, CaO, MgO, and TiO2 . PBS added bricks (B0–B50%, w/w) were casted and fired in the temperature range from 950 to 1050 °C and B5 bricks (1050 °C) showed the highest compressive strength (74 N/mm 2 ) and the lowest water absorption (2.1%). The modified bricks exhibited an improved ductile behavior and porosity restraining its deformation and/or distortion during firing and avoiding sudden failure of masonries. PBS imparted yellow coloration to bricks due to high CaO content, which can be an added benefit in decorative purposes. The bricks were tested for linear shrinkage behavior, volume of open pores, bulk density, and loss on ignition. Furthermore, the toxicity characteristic leaching procedure test confirmed an effective Pb, Cd Ni, and Zn fixation, and B20 bricks complied IS:1077:1992 class 12.5 and ASTM International.